Rural microcredit: Public policy instrument to guarantee food security in northeast Brazil (Research, Society and Development, 2024)
This article aims to analyze how the public policy of rural microcredit can contribute to providing food security for the northeastern population residing in the rural area. The hypothesis of this study consists of the following question “How can the granting of rural microcredit carried out by public banks, as a public policy tool, provide food security for the northeastern population?”. The descriptive methodology was used in this study, based on scientific publications, official government data and journalistic publications. It was found in this research that the microcredit public policy must be accessed by the most needy in an efficient way so that it can have effects on the food security of the northeastern population, especially those who live in the rural area.